Change in the inflammatory potential of diet over 10 years and subsequent mortality: the Multiethnic Cohort Study. Issue 1 (14th January 2023) - Park, Song-Yi; Lozano, Chloe P.; Shvetsov, Yurii B.; Boushey, Carol J.; Wirth, Michael D.; Shivappa, Nitin; Hébert, James R.; Haiman, Christopher A.; Wilkens, Lynne R.; Le Marchand, Loïc
Abstract: Dietary inflammatory potential assessed by the Dietary Inflammatory Index (DII ® ) has been associated with health outcomes. However, longitudinal changes in the DII in relation to health outcomes rarely have been studied. This study aimed to examine change in the DII score over 10 years and its association with subsequent mortality in the Multiethnic Cohort. The analysis included 56 263 African American, Japanese American, Latino, Native Hawaiian and White participants who completed baseline (45–75 years) and 10-year follow-up surveys, including a FFQ. Mean energy-adjusted DII (E-DII) decreased over 10 years in men (from −0·85 to −1·61) and women (from −1·80 to −2·47), reflecting changes towards a more anti-inflammatory diet. During an average follow-up of 13·0 years, 16 363 deaths were identified. In multivariable Cox models, compared with anti-inflammatory stable individuals, risk of all-cause mortality was increased with pro-inflammatory change in men (hazard ratio (HR) = 1·13, 95 % CI 1·03, 1·23) and women (HR = 1·22, 95 % CI 1·13, 1·32). Per one-point increase in E-DII score over time, HR was 1·02 (95 % CI 1·00, 1·03) for men and 1·06 (95 % CI 1·04, 1·07) for women ( P for heterogeneity < 0·001). While no heterogeneity by race and ethnicity was observed for men, the increased risk per one-point increase among women was stronger in non-Whites than in Whites ( P for heterogeneity = 0·004). Our findings suggest that a change towards a more pro-inflammatory diet is associated with an increased risk of mortality both in men and women, and that the association is stronger in women, especially non-White women, than in men.